2014
DOI: 10.5812/ircmj.12332
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of the Ethics Committees in Teaching Hospitals Affiliated With Mashhad University of Medical Sciences

Abstract: Background:During the last three decades, ethics committees have been formed with a growing trend. These committees have a satisfactory and effective impact on the pattern of patient care and its performance. The medical ethics committee is considered one of the most active committees in hospitals, having the aim of providing necessary approaches for the optimal use of the findings in empirical science and diagnostic treatment and observance of Islamic noble values in performing medical affairs.Objectives:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In a study done by Meraji et.al in hospitals of Mashhad universities, average of hospital committee bills was 4 -5 that is similar to our study ( Meraji et al, 2014 ). Our study shows that average of participants number in hospital committees in 2011 and 2012 is10 to 11 persons which coordinates the offered number of committee members in the most resources.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In a study done by Meraji et.al in hospitals of Mashhad universities, average of hospital committee bills was 4 -5 that is similar to our study ( Meraji et al, 2014 ). Our study shows that average of participants number in hospital committees in 2011 and 2012 is10 to 11 persons which coordinates the offered number of committee members in the most resources.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the importance of committees in planning and decision-making for current problems as well as preventing future problems, powerful and active committee members can improve committee efficiency (Rate of implemented bills improves). A study of Meraji et al in Mashhad showed that position of number of held sessions, rate of participants in sessions and distance among sessions were at medium but results in kind of bills and promotion of ethical values were at good level and also in the study of Meraji, presence of representative of university president in ethics committee was 28% that it shows importance of holding hospital committees sessions from view of related managers ( Meraji et al, 2014 ). Our study also shows that besides decreasing the number of hospital committees from 14 committees to 11 committees, the rate of hospital chief attendance in committees sessions in 2012 has been more than 2011 ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An effective CEC consultant also showed interest in organizational ethics [7], educating and guiding others on ethical issues [80,91,92] and aligning expectations and practice with institutional and CEC standards [82,86]. Some studies evaluated all members of the CECons as a whole [22,33,97] and their ability to provide a broad review of ethico-legal and moral considerations [73,98].…”
Section: Domains Assessedmentioning
confidence: 99%
“…The results of a study conducted in one of the major cities in Iran indicates that HECs are functioning as combined committees (85.7%) entitled ethics committee and religious principles. These committees are chaired by doctors (42.8%), hospital directors (2.5%), hospital managers (14.28%), and nurses (14.2%) in different educational hospitals (56). In this review, very few documents were found regarding other countries in the Middle East Region.…”
Section: Eastern Mediterranean Region Iranmentioning
confidence: 99%